SWOT Analysis of the Impact of Textile Factory Closures on Employment: A Study from an Islamic Economic Perspective - Shifa, Mutiara; Ardiansyah, Ardiansyah; Muliana, Muliana; Sari, Cindi Permata; Mustaqin, Al (Universitas Syiah Kuala, 2025)
This study analyzes the impact of textile factory closures on employment in Indonesia using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework integrated with the maqid al-sharah principles of Islamic economics. A descriptive qualitative method was applied, utilizing secondary data from BPS, the Ministry of Industry, and academic publications from 20182024. The results show that the main strengths of the textile industry lie in production capacity and labor absorption, while its weaknesses include dependence on imported raw materials and weak financial management. Opportunities arise from industrial downstream policies and local cultural-based products, whereas threats stem from global competition and economic instability. The integration of SWOT analysis with maqid al-sharah emphasizes justice, social responsibility, and workers welfare as essential elements in ensuring the sustainability of Indonesias textile industry.